Characterizing husbandry practices and breeding objectives of Sheko cattle owners for designing conservation and improvement strategies in Ethiopia - Bayou, E.; Haile, Aynalem; Gizaw, Solomon; Mekasha, Yoseph (2014)
A survey was conducted through single field visits and interviews with 360 respondents in selected districts of Bench Maji Zone, Southwestern Ethiopia to asses the Sheko cattle farming system, breeding practices, and identify cattle breeding goals and constraints for designing Sheko cattle conservation and improvement strategies. The total populations of Sheko cattle herd structure in the sampled districts within each PA obtained by counting directly on the field were estimated to be 2813.Under random mating, the inbreeding coefficient was higher in midland (1.72) than in lowland (1.35) agro ecological zones (AEZs). The mean Sheko cattle herd size per household was 1.09 in midland and 1.29 in lowland AEZs. About 93.9% and 88.3% of the households, respectively, in midland and lowland do not have breeding bull. Random mating predominates in both midland (87.2%) and lowland (85%) AEZs. The reported peak season of mixing of the different Sheko cattle herd within a village start after the crop aftermath (February to May) was picked from the cultivated land, whereas, beginning from main rainy season in June to the end of crop harvesting time usually on January smallholder farmers in both AEZs keep their cattle separately. The observed male to female mating ratio was 1:16.4 in midland and 1:8.6 in lowland. Sheko bulls were castrated at the age of 4.2 and 4.8 years in midland and lowland respectively. Appearance/conformation was the most important trait in choosing of breeding male for both midland and lowland small holder Sheko owners. Whereas, milk yield was the most important trait for the choice of breeding cows in both AEZs. The purpose of keeping Sheko cattle in midland area was for draught followed by milk, income, saving and dowry, in that order. In lowland agro ecology milk production, draught power, and income generation are the purposes for keeping Sheko cattle. In both AEZs feed shortage, disease and labor shortage were the most important cattle production constraints in that order. It has been found that an integrated system approach to breed conservation and improvement needs to incorporate traits sought by the cattle keepers, the multiple roles of cattle, and the existing traditional herding and breeding practices.